In vitro corrosion analyses of heat treated cobalt-chromium alloys manufactured by direct metal laser sintering. Issue 1 (19th January 2015) - Alifui-Segbaya, Frank; Lewis, Jeffrey; Eggbeer, Dominic; Williams, Robert John
Abstract : Purpose: – The purpose of this research paper is to compare corrosion data obtained from additive-manufactured heat-treated (HRx) and non-heat-treated (NHRx) cobalt-chromium (Co–Cr) alloys. Heat treatments are indicated as necessary in complex intra-oral framework production by additive manufacturing to remove accumulated thermal stresses. However, heat treatments have been linked to corrosion in cast dental alloys. Currently, there are few publications on this subject for laser-sintered dental alloys required for academic review. Design/methodology/approach: – Five rectangular specimens ( n = 5), each with a total surface area of 10.27 cm2, were fabricated for the two groups. Specimens were immersed in an artificial saliva solution suspended by a nylon thread for 42 days at 37°C. Readings for Co, Cr and molybdenum ions released into the solution were obtained using an atomic absorption spectrometer at 1-, 4-, 7-, 14-, 21-, 28-, 35- and 42-day intervals at a detection limit of one part per million. Test methods are in accordance with ISO 10271. Findings: – Results showed a higher ion release in the HRx sample, statistically significant at 99 per cent confidence level ( p < 0.01). A two-way ANOVA test conducted showed that there was a main effect of day and a main effect of finish, and there was also a significant interaction between these factors. Originality/value: – The study concludes that, although ion release in both samples was within the safe level recommended by ISO for the three major alloying elements, heat treatment, indeed, contributed extensively to the reduced corrosion resistance in the laser-sintered Co–Cr alloy. Further biocompatibility tests are recommended.